Cooling ceiling assisted by desk fans for comfort in hot-humid environment. (September 2017) - He, Yingdong; Wang, Xiang; Li, Nianping; He, Meiling; He, De; Wang, Kuan
Abstract: This study aims to investigate the effect of using cooling ceiling and desk fans on comfort in hot-humid environment. A series of experiments was conducted in an experimental room at 26, 28 and 30 °C (relative humidity was 70%). The obtained results indicate that the combination of cooling ceiling and desk fans reduced warm sensation and improved comfort in hot-humid environment, which mainly resulted from the improvement of local conditions of upper body parts. This combination also lowered humid sensation and improved perceived air quality but the local airflow by desk fans caused draft risk at 26 °C. Besides, cooling ceiling could only meet the 80% acceptable demand at 28 °C, while cooling ceiling and desk fans made more than 80% subjects feel acceptable at 28 and 30 °C. Also, the combination exerted more significant effects on increasing acceptability to both humid environment and air quality than using cooling ceiling alone. Besides, the preferences of subjects for cooler environment, stronger air movement and drier environment were significantly weakened under hot-humid conditions. In addition, the combination had potentials of energy conservation since it could extend acceptable range and reduce the energy for dehumidifying indoor air. Highlights: Experiments on the combination of radiant cooling and desk fans were conducted. The combination improved comfort of subjects under hot-humid condition. Acceptability of subjects to hot-humid environment was strengthened. Preference of subjects for cooler environment was weakened.